RISE: Disruptions in supply chains and a lesson from the COVID-19 pandemic: a retail perspective / Prof. Dr Jaafar Pyeman and Prof. Dr Veera Pandiyan Kaliani Sundram - Pyeman, Jaafar; Kaliani Sundram, Veera Pandiyan (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
The importance of supply chains has never seemed so vital before the age of COVID-19.